The use of simple muscle strength tests to reflect body compositions in elderly - Chokphukiao, Pakwipa; Poncumhak, Puttipong; Intarak, Roongnapa; Sooknuan, Thanat; Amatachaya, Pipatana; Thaweewannakij, Thiwabhorn; Somboonporn, Charoonsak; Amatachaya, Sugalya (Health Science, Science and Technology Reviews, 2021)
The study explored the correlation of three simple muscle strength tests (including grip strength test, five times sit-to-stand test, and upper limb loading during seated push-up test) and body compositions (including total skeletal muscle mass, bone mass, and fat mass) in 30 participants, aged 65 years and over. Participants were assessed using the three methods of muscle strength tests in a random order. Then, within 7 days, they were appointed to assess for their body compositions at a hospital. The correlation between outcomes of muscle strength tests and body compositions was analyzed using Pearson correlation coefficients and Spearman's correlation coefficient according to the data distribution. The findings indicated that grip strength test was significantly correlated with total muscle mass and bone mass (r=0.585-0.699, p<0.001). Five times sit-to-stand test significantly associated with the body fat mass (ρ= 0.471, p= 0.009), whereas the upper limb loading during seated push-up test was significantly related to all three body compositions (r=0.597-0.762, p<0.001). With their crucial roles for many bodily functions but the assessments for body compositions require a complex and costly machine, the present findings suggest the use of upper limb loading during a seated push-up test as a simple measure to assess and periodic monitor body compositions in elderly.